PENGGUNA TIKTOK DAN FEAR OF MISSING OUT (FoMO): (Studi Kasus Fenomena Tren Fashion Sepatu Branded Di Kalangan Murid SMAN 1 Polanharjo Pengguna Tiktok) - Aditya Prasetio; Lukas Maserona (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
The development of social media, particularly TikTok, has brought significant changes to consumption patterns and youth lifestyles, including among students at SMAN 1 Polanharjo. This application functions not only as a source of entertainment but also as a space for shaping fashion trends and guiding user preferences, especially in the context of Fear of Missing Out (FoMO). FoMO arises when individuals feel anxious about missing out on trends or social activities they observe on social media. This study aims to analyze how students at SMAN 1 Polanharjo interpret and respond to the trend of branded shoes going viral on TikTok within the framework of FoMO experiences. Using a qualitative approach with a case study method, this research explores the subjective experiences of six active TikTok users, based on five key characteristics of FoMO: the need for social connectedness, social comparison, self-validation, dependence on social media, and consumerism and trend culture. The results show that both followers of fashion-related TikTok accounts and non-followers experience FoMO, which contributes to their desire to follow branded shoe trends in order to gain social recognition and avoid feeling left out. In this context, social media serves as a space for identity construction and a site of social pressure related to consumer behavior among youth. Keywords: TikTok, Fear of Missing Out (FoMO), branded shoes, fashion trends, high school students